MODIFIED ZEOLITES IN GROUND WATER TREATMENT - Barloková, Danka; Ilavský, Ján; Sokáč, Marek (GeoScience Engineering, 2015)
There are presented results of technological experiments carried out in Water Treatment Plant Kúty. The goal of this study was to compare modified zeolite known as clinoptilolite (rich deposits of clinoptilolite were found in the region of East Slovakia in the 1980s) with the imported modified zeolite from deposit situated in Hungary. Klinopur-Mn and Klinomangan were used for removal of iron and manganese from ground water to meet the requirements of the Regulation of the Government of the Slovak Republic No. 496/2010 on Drinking Water. The materials observed exhibit different efficiencies of manganese removal from water, since the quality of the treated water play a major role (oxygen content and pH value). In the case of the removal of the iron from the water, the quality of the raw water is not a limiting factor; both materials removed Fe from the water to below the limit value (0.20 mg.l-1).